Experimental Study on Pressure-Deformation-Contact Resistance Characteristics of Converter Transformer Valve Side Casing Louver Contacts - Shihong Hu; Zhicheng Huang; Jiahui Chen; Chi Yuan; Bozhang Feng; Tao Zhao; Yunpeng Liu (IEEE Access)
The performance degradation of oil-immersed louver contacts are the main reason for the DC resistance exceeding the standard on the valve side of UHV converter transformers. In this paper, a louver contact performance test platform is designed and built according to the actual assembly structure of the louver contact. The relationships between pressure, deformation and contact resistance of the louver contacts are measured and obtained by utilizing the louver contact test platform. The characteristics between the parameters of contact resistance, pressure and load current are investigated based on the test platform. The results show that the contact resistance decreases exponentially with the increase of the pressure on the louver contacts, and the contact resistance decreases with the increase of load current applied on the louver contacts. At the same time, based on the test results, the change characteristics are analysised of the surface shrinkage resistance and film layer resistance of the contact piece. The obtained conclusions can provide a practical basis for the design of electric contact components of power transformer bushings and fault analysis research.